Art of Dreamworks Trolls - Schmitz, Jerry; DreamWorks Animation (Petaluma, California : Cameron + Company, 2016)
"From the creators of Shrek comes DreamWorks' Trolls -- an irreverent animated comedy that gives a colorful, personality-filled twist to the iconic hair-raising pop culture phenomenon ... the filmmakers at DreamWorks created hundreds of pieces of concept and production art, developing an outrageously colorful, tactile look for the Trolls, which they juxtaposed against the urban-inspired look of the Bergens."--Back cover.
-- Foreword -- Introduction -- Meet the trolls -- Sequence 1100 -- Welcome to Bergentown -- Finale -- Acknowledgments -- Colophon.
Keywords: Animated films -- United States -- 21st century; Artists' preparatory studies; Storyboards; Trolls